2007
DOI: 10.1248/cpb.55.1600
|View full text |Cite
|
Sign up to set email alerts
|

Tricalysiosides P-U: Ent-kaurane Glucosides and a Labdane Glucoside from Leaves of Tricalysia dubia OHWI

Abstract: The approximately 50 species of Tricalysia (Syn. Canthium) are found in subtropical and tropical areas of Asia and Africa. Some species are used for medicinal purposes, e.g. the roots, leaves, and stem bark of Canthium subcordatum are used as folk medicines in Africa. 1)Tricalysia dubia (LINDL.) OHWI (Rubiaceae) is an evergreen shrub or tree that grows to a height of about 2-4 m. It is distributed in the south of China, Taiwan, and Okinawa. 2)In the course of our study on Okinawa's promising resource plants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Only two additional furostanols, anguivioside XI 17 and solasodoside F, 18 with a deformed F ring have been reported previously. The nine known constituents were isolated previously from different genera of Solanaceae (Lycium chinense), 9 Arecaceae (Borassus f labellifer 5 and B. decumbens 6 ), Rubiaceae (Tricalysia dabia), 10 and Urticaceae (Urtica dioica) 7 families, but are first reported herein from S. violaceum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Only two additional furostanols, anguivioside XI 17 and solasodoside F, 18 with a deformed F ring have been reported previously. The nine known constituents were isolated previously from different genera of Solanaceae (Lycium chinense), 9 Arecaceae (Borassus f labellifer 5 and B. decumbens 6 ), Rubiaceae (Tricalysia dabia), 10 and Urticaceae (Urtica dioica) 7 families, but are first reported herein from S. violaceum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2). Comparison of the carbon shifts of C-2 and C-3 of 1 with those of the labdane 3-O-glucoside, tricalysioside U (8) (Otsuka et al, 2007) and the ent-labdane 3-O-glucoside (9) (Shen et al, 2006) (Table 1) clearly showed that microtropioside A belonged to the ent-labdane series. The configuration of the C-14 hydroxyl group was deduced to be  on the basis of significant NOE interactions between H-11 axial and H-14.…”
Section: --Fig 1 -mentioning
confidence: 98%
“…The monoterpene linalool and a number of its hydroxylated derivatives are secondary metabolite occurring in different vegetal species [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Although both enantiomeric forms of linalool are present in nature, (R)-linalool (1), its 6,7-dihydroxylated derivatives (2a-5a) and a number of their glycoside derivatives ( Figure 1) are more common than the corresponding (S)-linalool deriving monoterpenes.…”
Section: T H Ementioning
confidence: 99%